علمي التاريخ والجغرافيا في إقليم شرق الأندلس خلال عصري المرابطين والموحدين - بواشرية, بلقاسم (University of Eloued جامعة الوادي, 2018)
يعالج موضوع البحث أنموذجا من العلوم الاجتماعية، وهما التاريخ والجغرافيا، اللّذين عرفا تطورا ملحوظا على أيدي علماء مؤرخون وجغرافيون اشتهرت بهم منطقة شرق الأندلس، خاصة مدينة المرية خلال عهدي المرابطين والموحدين، إذ كشف هؤلاء العلماء عن مناهج وأساليب تميزوا بها في نقل هذه العلوم تدريجيا من مرحلة إلى أخرى حتى أضحت ذات شأن في الحقل الفكري والثقافي خلال فترة الدراسة. The subject of reseach deals with a model of the social scionces namly history and geography, whith were known to be a remarkable development by historians and geographers who were famous for their region of Eest Andalusia, especially the city of Almeria during the periods of Almoravid and Almohaden, as these scientste revealed methods and methods characterized by the transfer of these sciences gradually from one stage to another even it became important in the field of imellectual and cultural during the study period.
Keywords: التاريخ الجغرافيا شرق الأندلس المرابطين الموحدين